2016
DOI: 10.1093/mnras/stw612
|View full text |Cite
|
Sign up to set email alerts
|

Drifting asteroid fragments around WD 1145+017

Abstract: We have obtained extensive photometric observations of the polluted white dwarf WD 1145+017 which has been reported to be transited by at least one, and perhaps several, large asteroids with dust emission. Observation sessions on 37 nights spanning 2015 November to 2016 January with small to modest size telescopes have detected 237 significant dips in flux. Periodograms reveal a significant periodicity of 4.5004 hours consistent with the dominant ("A") period detected with K2. The folded light curve shows an h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
155
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(165 citation statements)
references
References 31 publications
9
155
1
Order By: Relevance
“…Subsequent passes further degrade the debris and it eventually embodies a disc geometry. Vanderburg et al (2015) have recently identified the first disintegrating asteroid around the dusty WD 1145+017 (see also Gänsicke et al 2016;Rappaport et al 2016), providing support to this interpretation. The signature of a disc orbiting a WD is excess emission in the infrared due to the reprocessed light from this dust.…”
Section: Introductionmentioning
confidence: 80%
“…Subsequent passes further degrade the debris and it eventually embodies a disc geometry. Vanderburg et al (2015) have recently identified the first disintegrating asteroid around the dusty WD 1145+017 (see also Gänsicke et al 2016;Rappaport et al 2016), providing support to this interpretation. The signature of a disc orbiting a WD is excess emission in the infrared due to the reprocessed light from this dust.…”
Section: Introductionmentioning
confidence: 80%
“…Subsequent photometric monitoring has revealed significant evolution of the transit depths and morphologies Rappaport et al 2016;Croll et al 2017). Xu et al (2016) presented high-resolution spectra of WD 1145+017 that showed circumstellar gas lines were present in several metal species with depths ≈10%-30% below the continuum.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for multiple Ceres-mass and lower co-orbital bodies with orbital periods of just about 4.5 h, the resulting orbital period deviations due to their mutual perturbations are of the order of seconds (Gurri et al 2017;Veras, Marsh & Gänsicke 2016b). This deviation is observationally relevant for the WD 1145+017 system Gary et al 2016;Rappaport et al 2016), but only because these orbits are so compact. Mutual perturbations amongst moons are primarily important during the formation of the moons themselves and their subsequent evolution around their parent planet; in our Solar system, there exist several relevant examples (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…A recent success is WD 1145+017 (Vanderburg et al 2015), a white dwarf which is both polluted and bears a debris disc, and which has recently been shown to also host disintegrating planetesimals. Hourly changes in the shape and depth of the transit light curves of the white dwarf WD 1145+017 have invigorated the post-main-sequence planetary community, motivating a large-scale observational effort Croll et al 2016;Gänsicke et al 2016;Gary et al 2016;Rappaport et al 2016;Redfield et al 2016;Xu et al 2016) and dedicated attempts to explain these observations (Gurri, Veras & Gänsicke 2017;Veras et al 2016c). The parallel understanding of the state-of-the-art dynamical and theoretical aspects of post-mainsequence planetary science is summarized in Veras (2016a).…”
Section: Introductionmentioning
confidence: 99%